1-Benzoyl-3-[(2-benzylsulfanyl)phenyl]thiourea - Bhattacharjee, Tirtha; Gogoi, Prasanta; Puranik, Vedavati G.; Gawade, Rupesh L.; Barman, Pranjit (Acta Crystallographica Section C-Crystal Structure Communications, 2012)
In the title compound, C21H18N2OS2, a strong intramolecular N-H center dot center dot center dot O hydrogen bond [N center dot center dot center dot O = 2.642 (3) angstrom] between the amide N atom and the benzoyl O atom forms an almost planar six-membered ring in the central part of the molecule. In the crystal, molecules are packed through weak N-H center dot center dot center dot S interactions. Intra- and intermolecular hydrogen bonds and van der Waals interactions are the stabilizing forces for the crystal structure.